Analisis Pesan Dakwah Pada Novel Bujang dan Jenderal Portugis Karya Harlis Kurniawan - Dinayatur Riza; Muhammad Nur Kholish Ar; Ahmad Asrof Fitri (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2024)
The rise of Islamophobia worldwide is often fueled by ignorance and negative stereotypes about Islam. This situation calls for more effective educational efforts to counter misinformation and restore the image of Islam as a blessing for all, or Rahmatan lil 'Alamin. In response to this challenge, da'wah (Islamic preaching) through literature, especially novels, offers a way for readers to gain new perspectives and understand the complexities of religious life through engaging narratives that do not come across as patronizing. This study aims to identify the da'wah messages in Harlis Kurniawan's novel Bujang and Portuguese General and analyze the most dominant themes within the text. The novel serves as a potential medium for educating people, including non-Muslims, about the true teachings of Islam. The research employs a descriptive quantitative approach using content analysis. The data analysis involves categorizing the content, evaluating it through judges' assessments, and calculating the findings using Microsoft Excel and the Slovin formula, followed by interpretation of the results. The result of this study shows that the novel possesses 37.66% message of morality which is very dominant, 32.46% sharia messages, and of 29.88% aqida messages.